Hydroxy Piperlongumines: Synthesis, Antioxidant, Cytotoxic Effect on Human Cancer Cell Lines, Inhibitory Action and ADMET Studies. Issue 38 (9th October 2020) - Subramani, Muthuraman; Ramamoorthy, Gayathri; Hemaiswarya, Shanmugam; Waidha, Kamran; Brindha, J.; Balamurali, M. M.; Doble, Mukesh; Rajendran, Saravanakumar
Abstract: Piperlongumine, an anticancer natural product, was sequentially demethylated to obtain mono, di and trihydroxy piperlongumines. The hydroxy piperlongumines were evaluated for cytotoxic effect on five human cancer cell lines (kidney, skin, cervical, breast, and lung) in vitro. Results from cytotoxic and cell growth inhibition studies showed monohydroxy piperlongumine (MHPL) was the most active of the series, exhibited potent cytotoxic effect on all the tested cell lines. Flow cytometry analysis shows MHPL inhibited cell cycle progression of HeLa cells in the S phase, indicated that it inhibits the DNA replication process. Fluorescence staining indicated MHPL treated cells were apoptotic. MHPL upregulated the apoptotic genes (caspase‐3, −8, Bax, and p53) and downregulated anti‐apoptotic gene (Bcl‐2). The antioxidant study revealed that hydroxy piperlongumines are effective antioxidants. For MHPL, all the molecular descriptors were within the range of 95 % of approved drugs suggesting high druglikeliness. Our results suggest that MHPL could be developed as a potential lead molecule for cancer therapy. Abstract : Hydroxy piperlongumines were synthesized from a anticancer natural product, piperlongumine. Monohydroxy piperlongumine (MHPL) exhibited high cytotoxic efffect against five human cancer cell lines. MHPL is a potent antioxidant, upregulates apoptotic genes and down regulate anti‐apoptotic gene in HeLa cells.